Covid19 pandemic impacted ianternet use and anxiety among general public during covid19 pandemic in Pakistan - Maryam Pyar Ali Lakhdir; Khan, Malik Muhammad Hamza; Fauzia Basaria Hasnani; Ghazal Peerwani; Muhammad Talha Nawaz; Ayesha Nasir Hameed; Meher Angez; Apsara Ali Nathwani; Syed Iqbal Azam (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the association between internet use and anxiety among people during the coronavirus disease-2019 pandemic. Method: The cross-sectional study was conducted across Pakistan from January 14 to February 21, 2021, which was the active phase of the coronavirus disease-2019 pandemic in Pakistan. The participants were aged at least 13 years having internet access regardless of gender or their location across Pakistan. The anonymous web-based survey was conducted using a questionnaire generated on Google Forms and disseminated through various social media platforms and WhatsApp groups. Anxiety symptoms were screened using the Depression, Anxiety and Stress Scale-21, while the Young Internet Addiction Test was used to evaluate symptoms of internet addiction. Data was analysed using STATA 16. Results: Of the 1,145 subjects, 686(60%) were females and 459(40%) were males. A total of 257(22.5%) participants were found to have extremely severe anxiety and internet usage pattern was significantly associated with the level of anxiety (p<0.05). Age, gender, social class and marital status were not significantly different (p>0.05), while family income and area of living were significantly different (p<0.05) in terms of anxity levels. . The odd of addictive internet use was 10.2 (95% confidence interval: 5.7-18.5) times greater in extreme anxiety individuals compared to individuals having no anxiety after controlling for other sociodemographic, health-related, behavioral and environmental factors during the pandemic. Conclusion: A significant association of anxiety was found with internet addiction during the coronavirus disease-2019 pandemic. Key Words: Internet addiction, Anxiety, Pandemic, COVID-19, Low-income countries.